Suppression of degradation for lithium iron phosphate cylindrical batteries by nano silicon surface modification. Issue 53 (4th July 2017) - Yang, Wenyu; Wang, Zhisheng; Chen, Lei; Chen, Yue; Zhang, Lin; Lin, Yingbin; Li, Jiaxin; Huang, Zhigao
Abstract : Si surface modification gets improved electrochemical performances for 18 650 cylindrical cells, especially at elevated temperature, which is attributed to the fact that Si can enable the LiFePO4 electrodes to suppress battery degradation. Abstract : Nano-scale silicon particles were successfully decorated uniformly on a LiFePO4 @C electrode through utilization of spray technique. The electrochemical measured results indicate that the Si surface modification results in improved electrochemical performances for commercial 18 650 cylindrical batteries, especially at elevated temperature, which is attributed to the fact that Si introduction can enable the LiFePO4 electrodes to suppress cylindrical battery degradation. Based on the analysis of structural characterization, it is revealed that the battery cathode with Si modification retains a better LiFePO4 phase and exhibits less Li + loss. In addition, the negative electrode of the battery contains a better graphite carbon structure and a thinner thickness of SEI film due to Si decoration. Furthermore, the related high-temperature aging and degradation mechanisms of the batteries were discussed.